(untitled) (Experimental biology, 2015)
Formation of drought-resistant samples of wheat includes selection of parental pairs for the hybridization, combining potential stability to a drought and high productivity; an estimation of drought resistance with use of laboratory methods; selection of drought-resistant samples in field stressful dry conditions and an ecological estimation of perspective drought-resistant samples. For the first time it is experimentally shown, that selection of perspective drought-resistant samples with use of laboratory methods, and then their field test in stressful conditions and wide use of an ecological estimation of perspective samples allows to reach for short time of positive results and to formation drought-resistant cultivars of wheat.